Analisis penerapan nilai karakter gemar membaca melalui budaya literasi pada peserta didik kelas III sekolah dasar - Nurifatul Elya Noviyanti; Peduk Rintayati; Fadhil Purnama Adi (Didaktika Dwija Indria, 2023)
This study aims to describe the application of the character values of reading fondness through third grade literacy culture. This research uses qualitative research methods and uses a case study approach. The subjects in this study were principals, teachers and third grade students. The focus of this research is application of the values of reading fondness characters through literacy culture which is divided into three stages, namely the habituation stage, the development stage, and the learning stage. The data used is the literacy program of SDN Tunggulsari 1, the data sources are the principal, homeroom teacher, and third grade students. Data collection techniques used are observation, interviews, and documentation. To test the validity of the data, the researcher used source triangulation and technique triangulation. This study uses the Miles and Huberman model analysis technique, with components of data condensation, data presentation, and drawing conclusions. The results showed that the application of the character values for the love of reading was carried out through: 1) the habituation stage by reading books 15 minutes before learning began. 2) the development stage, namely the existence of a library visit schedule. 3) the learning stage, namely the use of literacy strategies to support learning.